Microbial Disruption Indices in the Fecal Microbiome Predicting Acquisition of Multidrug-Resistant Organisms in Nursing Homes. (4th October 2017) - Araos, Rafael; Ugalde, Juan; D'agata, Erika M
Abstract: Background: Residents of nursing homes (NH) are frequently exposed to antimicrobials and constitute a reservoir of multidrug-resistant organisms (MDRO). Microbiome dysbiosis has been associated with adverse clinical outcomes including MDRO colonization and infection. This study aimed to characterize specific features in the fecal microbiome (microbial disruption indices) predicting MDRO acquisition in residents of NH. Methods: Residents in 35 NH from the Boston area, exposed to antimicrobials, were included in the study. Demographic and clinical characteristics, and rectal swabs were collected every three months for up to 12 months or until death to determine MDRO acquisition (negative baseline swab and at least one subsequent swab positive for MDRO). Rectal specimens were screened for MDRO by using conventional cultures. Additionally, the V4 region of the 16S rRNA gene was sequenced for assessing the fecal microbiome (Illumina MiSeq platform). Filtering, dereplication, sample inference, chimera checking, and merging of pair-end reads were performed using DADA2. The exploratory and inferential analyses were done using phyloseq. Fecal microbial diversity and composition was compared between patients that acquired MDRO or not. Results: A total of 80 residents had at least two serial rectal samples and were exposed to antimicrobials. Among them, 28 (35%) acquired MDRO. Microbial diversity (Shannon index) was similar between those that acquired MDRO or not (MDRO+ and MDRO-, respectively). The β diversity analysis (UniFrac distances) did not show specific sample clustering according to MDRO status (Figures 1 and 2). The analysis of differentially abundant features showed higher relative abundance of Akkermansia muciniphila among MDRO- patients, whereas Blautia spp. was more abundant among those that acquired MDRO (Figure 3). Conclusion: Differential abundance of key bacterial taxa, such as Akkermansia muciniphila and Blautia spp. may be future biomarkers predictive of MDRO acquisition. Identification and standardization of microbial disruption indices may provide important data to guide future innovative public health strategies aimed at limiting MDRO acquisition and dissemination. Disclosures: J. Ugalde, uBiome: Employee, Salary.